Keterkaitan Pola Guna Lahan dengan Pola Pergerakan Layanan Transportasi Online di Kawasan Universitas Diponegoro - Adam, Khalid; Manullang, Okto Risdianto (Jurnal Pembangunan Wilayah dan Kota, 2020)
Online transportation has become popular among the public because of its different character than public transportation that was previously available. Therefore, the question in this study is how the influence of land use patterns on the existence of online transportation in the Education Area of Diponegoro University ?. The expected results are in the form of information regarding the effect of land use on online transportation so as to be able to issue policy recommendations related to online transportation. The analysis was carried out by overlaying the pattern of use of the exiting land with the movement pattern of the motorcycle taxi service. The data used in the analysis is divided into two based on time, namely at weekends and weekdays. Based on observation, it was found that 759 movements and the results of overlays carried out with existing land use patterns showed that the highest pattern of demand occurred in residential and boarding areas, educational areas, and commercial areas. This explains that these areas have a large influence on the movement of online transportation facilities.Â